Thrombopoietic potential and serial repopulating ability of murine hematopoietic stem cells constitutively expressing interleukin 11. - Hawley, R G (1996)
Based on transplantation studies with bone marrow cultured under various conditions, a role of interleukin 11 (IL-11) in the self-renewal and/or the differentiation commitment of hematopoietic stem cells has been indicated. To better evaluate the in vivo effects of IL-11 on stem/progenitor cell biology, lethally irradiated mice were serially transplanted with bone marrow cells transduced with a defective retrovirus, termed MSCV-mIL-11, carrying the murine IL-11 (mIL-11) cDNA and the bacterial neomycin phosphotransferase (neo) gene. High serum levels (i.e., > 1 ng/ml) of mIL-11 in all (20/20) primary and 86% (12/14) of secondary long-term reconstituted mice, as well as 86% (12/14) of tertiary recipients examined at 6 weeks posttransplant, demonstrated persistence of vector expression subsequent to transduction of bone marrow precursors functionally definable as totipotent hematopoietic stem cells. In agreement with results obtained with human IL-11 in other myeloablation models, ectopic mIL-11 expression accelerated recovery of platelets, neutrophils, and, to some extent, total leukocytes while preferentially increasing peripheral platelet counts in fully reconstituted mice. When analyzed 5 months posttransplant, tertiary MSCV-mIL-11 recipients had a significantly greater percentage of G418-resistant colony-forming cells in their bone marrow compared with control MSCV animals. Collectively, these data show that persistent stimulation of platelet production by IL-11 is not detrimental to stem cell repopulating ability; rather, they suggest that IL-11 expression in vivo may have resulted in enhanced maintenance of the most primitive hematopoietic stem cell compartment. The prolonged expression achieved by the MSCV retroviral vector, despite the presence of a selectable marker, contrasts with the frequent transcriptional extinction observed with other retroviral vectors carrying two genes. These findings have potentially important implications for clinical bone marrow transplantation and gene therapy of the hematopoietic system.